A new era Scottish modern art 1900-1950 - Strang, Alice 1973- (National Galleries of Scotland, 2017)
A New Era takes its name from the group established in Edinburgh in 1939 to show surreal and abstract work by its members, including William Gillies and Tom Pow. The book will reveal Scottish artists' engagement with and interpretation of the great movements of European Modern art, from Fauvism and Expressionism, to Cubism, Art Deco, Abstraction and Surrealism. Beginning with J.D. Fergusson's move to Paris in 1907 where he became entrenched in the French capital's avant-garde art scene and ending with the Arts Council of Great Britain's controversial acquisition of William Gear's Autumn Landscape from the Festival of Britain in 1951, 'A New Era' reveals Scottish artists' commitment to the progress of art from pre-World War One Paris to London in the 1920s, Edinburgh in the 1930s, Glasgow during the early 1940s and the emergence of a new generation including Wilhelmina Barns-Graham and Alan Davie after World War Two. Exhibition:Scottish National Gallery of Modern Art, Edinburgh, UK (02.12.2017 - 10.06.2018)
To accompany the exhibition ... held at the Scottish National Gallery of Modern Art, Edinburgh, from 2 December 2017 to 10 June 2018
Keywords: Geschichte 1900-1950; Kunst; Schottland; Ausstellungskatalog -- Scottish National Gallery of Modern Art -- 02.12.2017-10.06.2018 -- Edinburgh; Bildband